Fixed Point Theorems for Multivalued Nonself G-Almost Contractions in Banach Spaces Endowed with Graphs. (31st January 2017) - Tiammee, J.; Charoensawan, P.; Suantai, S.
Abstract : In this paper, we prove some fixed point theorems for multivalued nonself G -almost contractions in Banach spaces with a directed graph and give some examples to illustrate our main results. The main results in this paper extend and generalize many known results in the literature therein.